Culturally responsive interventions : innovative approaches to working with diverse populations - Ancis, Julie R. (Brunner-Routledge, 2004)
This book fills the widening gap in multicultural literature by providing specific culture-centered interventions. The first section of the text highlights culturally based interventions.